Perancangan Aplikasi Perbesaran Citra dengan Metode Proyeksi Cahaya - Zarcelonia, Zolyviade (Jurusan Informatika Universitas Tanjungpura, 2014)
The research conducted in this thesis is to try to analyze and verify whether the assumed working principles projector to enlarge the image to produce a magnified image. The method is designed based on the principles of light projection in its design and fully utilize the unique properties of light which always propagates through straight lines and in all directions.The result of this research is a light projection method, which is divided into two phases: a projection phase of the original image pixel to image results, which is an early stage light projection method, in which all of the original image that is projected onto the enlarged image of the results, and the filling empty pixels (resampling) phase, which fills the pixels that have not been defined (resampling). Magnification with light projection method produces enlarged images which are similar to the results of bilinear magnification method.Keywords -